Conservation of higher aquatic flora in the Kharkiv region - Kazarinova, H. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Based on the results of field research, inventory of CWU herbarium collections and study of scientific sources it was carried out the sozological assessment of rare plant species as a part of the higher aquatic flora of the Kharkiv region according to generally accepted criteria of rarity. It has been found that four species (Salvinia natans (L.) All., Trapa natans L., Utricularia intermedia Hayne, U. minor L.) are listed in the Red Book of Ukraine, the first two of which are in the Annex I of Bern Convention. The European Red List of Vascular Plants includes three species (Potamogeton acutifolius Link, P. rutilus Wolfg., Trapa natans), which have the conservation status “Near Threatened”. 27 plant species are in the Red List of Aquatic Macrophytes of Ukraine and 22 species are included in the Regional Red List of the Kharkiv region. It has been revealed that populations of six rare species (Batrachium aquatile (L.) Dumort., Potamogeton obtusifolius Mert. et Koch, P. rutilus Wolfg., Scirpus triqueter L., Vallisneria spiralis L., Wolffia arrhiza (L.) Horkel ex Wimmer) are on the border of the range. By the uniqueness for the region, one species (Salvinia natans) is considered as rare for Europe, 26 species are rare at the state level and 10 species are rare at the regional level. For 22 species there are known from one to five locations in the region. By the size of the habitat area, the most of cenopopulations of species occupy small areas (for 27 species it is less than 5 hectares). At present the location of 6 species has not been confirmed (Ceratophyllum tanaiticum Sapjeg., Potamogeton gramineus L., P. obtusifolius Mert.et W.D.J.Koch, P. praelongus Wulfen, P. sarmaticus Mäemets, Trapa natans). It has been established that populations of only 8 species are represented quite fully at the natural reserve areas of the region. On the basis of autphytosozological analysis we propose to include 22 species of vascular plants in the Regional Red List of the Kharkiv region and to exclude from it two species: Utricularia intermedia, which is in the Red Book of Ukraine and has the conservation status at the state level, and Vallisneria spiralis L., which is considered as adventive species.